2020
DOI: 10.1101/2020.06.25.172155
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Abundance and nuclear antigen reactivity of intestinal and fecal Immunoglobulin A in lupus-prone mice at younger ages correlate with the onset of eventual systemic autoimmunity

Abstract: Our recent studies, using (SWRxNZB)F1 (SNF1) mice, showed a potential contribution of the gut microbiota and pro-inflammatory immune responses of the gut mucosa to systemic autoimmunity in lupus. Here, using this mouse model, we determined the abundance and the nAg reactivity of IgA antibody produced in the intestine under lupus susceptibility. Intestinal lymphoid tissues from SNF1 mice, females particularly, showed significantly higher frequencies of nAg (dsDNA and nucleohistone) reactive IgA producing B cell… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
17
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 63 publications
(102 reference statements)
7
17
0
Order By: Relevance
“…Importantly, anti-DNA antibodies of IgA class are found in the serum of patients with SLE [18][19][20][21][22][23]. These reports along with our studies [13,14,24] showing pro-inflammatory immune phenotype and higher plasma cell frequency in the intestine, and higher abundance and nAg reactivity of fecal IgA in female SNF1 mice at preclinical stages suggested that the degree of IgA secretion in the gut lumen could be indicative of systemic autoimmune progression. However, whether these features are unique to SNF1 mice or ubiquitous to other preclinical models of lupus [such as MRL/lpr, NZM2328, NZM2410, (NZBxNZW-F1) NZB/WF1] is not known.…”
Section: Introductionsupporting
confidence: 59%
See 4 more Smart Citations
“…Importantly, anti-DNA antibodies of IgA class are found in the serum of patients with SLE [18][19][20][21][22][23]. These reports along with our studies [13,14,24] showing pro-inflammatory immune phenotype and higher plasma cell frequency in the intestine, and higher abundance and nAg reactivity of fecal IgA in female SNF1 mice at preclinical stages suggested that the degree of IgA secretion in the gut lumen could be indicative of systemic autoimmune progression. However, whether these features are unique to SNF1 mice or ubiquitous to other preclinical models of lupus [such as MRL/lpr, NZM2328, NZM2410, (NZBxNZW-F1) NZB/WF1] is not known.…”
Section: Introductionsupporting
confidence: 59%
“…We also examined if fecal IgA features at younger ages show a correlation with the eventual nAg reactivity of serum IgG in males and females. We found that fecal IgA in MRL/lpr, NZM2328, NZM2410, NZB/WF1 mice, similar to SNF1 mice [14], shows varying degrees of age dependent increase in the abundance and nAg reactivity. Fecal IgA in these mice showed considerable levels of nAg reactivity starting at as early as juvenile age.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations